THE INFLUENCE OF E-SERVICE QUALITY, E-TRUST AND E-WOM ON LIVE STREAMING PURCHASE DECISIONS - Listianayanti, I Gusti Ayu Priska; Wisudawati , Ni Nyoman Sri; Syarofi, Muhammad (STIE PGRI Dewantara Jombang, 2023)
The development of the digital world has brought various changes in lifestyles and human activities, including e-commerce. E-commerce activities open opportunities for companies to be more innovative in attracting consumers, one of which is utilizing the e-live streaming buying feature. This study aims to determine the effect of e-service quality, e-trust, and e-word of mouth on purchasing decisions in e-commerce live streaming. This study uses a quantitative research approach. The population of this study was e-commerce users in Denpasar City, and the sample used was 150 e-commerce users. The data used is primary data in the form of a questionnaire. The data analysis tool used is SEM PLS. The study results show that E-service quality, E-trust, and E-WOM positively affect purchasing decisions in e-commerce live streaming. E-service quality has no significant effect on E-WOM. E-trust has a positive effect on e-WOM. E-WOM cannot mediate e-service quality for purchase decisions on e-commerce live streams. E-WOM can mediate e-trust for purchasing decisions in e-commerce live streaming.